Nanoscale imaging and control of altermagnetism in MnTe - Amin, O J; Dal Din, A; Golias, E; Niu, Y; Zakharov, A; Fromage, S C; Fields, C J B; Heywood, S L; Cousins, R B; Maccherozzi, F; Krempaský, J; Dil, J H; et al. (Nature, 2024)
Nanoscale detection and control of the magnetic order underpins a spectrum of condensed-matter research and device functionalities involving magnetism. The key principle involved is the breaking of time-reversal symmetry, which in ferromagnets is generated by an internal magnetization. However, the presence of a net magnetization limits device scalability and compatibility with phases, such as superconductors and topological insulators. Recently, altermagnetism has been proposed as a solution to these restrictions, as it shares the enabling time-reversal-symmetry-breaking characteristic of ferromagnetism, combined with the antiferromagnetic-like vanishing net magnetization1-4. So far, altermagnetic ordering has been inferred from spatially averaged probes4-19. Here we demonstrate nanoscale imaging of altermagnetic states from 100-nanometre-scale vortices and domain walls to 10-micrometre-scale single-domain states in manganese telluride (MnTe)2,7,9,14-16,18,20,21. We combine the time-reversal-symmetry-breaking sensitivity of X-ray magnetic circular dichroism12 with magnetic linear dichroism and photoemission electron microscopy to achieve maps of the local altermagnetic ordering vector. A variety of spin configurations are imposed using microstructure patterning and thermal cycling in magnetic fields. The demonstrated detection and controlled formation of altermagnetic spin configurations paves the way for future experimental studies across the theoretically predicted research landscape of altermagnetism, including unconventional spin-polarization phenomena, the interplay of altermagnetism with superconducting and topological phases, and highly scalable digital and neuromorphic spintronic devices3,14,22-24.